Design a mechanism Like flapping hummingbird wings - Javareshkian, Mohamad Hasan; Vashani, Mehdi Behnam (Ciência e Natura, 2015)
Hummingbirds have been considered because they have high maneuverability. Making an example of this type of bird needs to observe the kinematic and aerodynamic issues of the bird’s flight. In this article the locus of attack angle and instantaneous elevation is studied to be used for constructing a sample of birds. At first, the charts offered in the article of bird’s flight was digitized and by using MATLAB software was fitted to the shape of a sinusoidal equation to be comparable with designed mechanisms. The designed mechanisms have three variables that by using EES software the motion equation has been approached. Then by the Lagrange Interpolation the effect of each variable in the equation of motion mechanism obtained. Finally by using EES software these equation is solved and the amount of the variables was calculated.